2012
DOI: 10.1186/1752-1947-6-363
|View full text |Cite
|
Sign up to set email alerts
|

Static winging of the scapula caused by osteochondroma in adults: a case series

Abstract: IntroductionAlthough palsy of the long thoracic nerve is the classical pathogenesis of winging scapula, it may also be caused by osteochondroma. This rare etiopathology has previously been described in pediatric patients, but it is seldom observed in adults.Case presentationWe describe three cases of static scapular winging with pain on movement.Case 1 is a Caucasian woman aged 35 years with a wing-like prominence of the medial margin of her right scapula due to an osteochondroma originating from the ventral o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
(46 reference statements)
0
15
0
4
Order By: Relevance
“…Mrad-Dali et al, reported 7 cases out of 95 cases [3]. About 45 cases were also published separately by different authors [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Ventral localization like our case was repoted in two cases [19].…”
Section: Discussionmentioning
confidence: 72%
“…Mrad-Dali et al, reported 7 cases out of 95 cases [3]. About 45 cases were also published separately by different authors [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Ventral localization like our case was repoted in two cases [19].…”
Section: Discussionmentioning
confidence: 72%
“…In these 20 articles, some reported surgical techniques. [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Similarly, our patient also had snapping scapula and pseudo-winging symptoms. However, perioperative images and radiological studies were demonstrative and didactic.…”
Section: Discussionmentioning
confidence: 99%
“…Plain radiographs (anteroposterior and lateral view) of the leg with knee revealed a large cauliflower-like growth arising from proximal fibula ( Figure 4 [13][14][15][16][17][18][19] 15 articles (except surgical technique reports) [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] 14 articles in literature [20][21][22][23][24][25][26][27][28][29][30][31][32][33] 14 articles in literature [20][21][22][23][24][25][26][27][28][29][30][31][32]…”
Section: Case Reportsmentioning
confidence: 99%
“…Mechanical effects of impingement are limited range of motion, friction and trigger tendons or ligaments and early osteoarthritis. The scapula is involved in 3.0 to 4.6% of complications [7,8]. Usually located at the anterior surface of the scapula, they are often symptomatic.…”
Section: Impingementmentioning
confidence: 99%